Influence of forest road, road‐surfacing material and stand age on floristic diversity and composition in a nutrient‐poor environment. Issue 3 (21st December 2012) - Bergès, Laurent; Chevalier, Richard; Avon, Catherine
Abstract: Questions: How did the presence of forest roads modify plant diversity and composition in a nutrient‐poor environment? What was the effect of the use of limestone gravel as road surfacing material? How did floristic succession vary between roadside and forest interior? Location: State Forest of Orléans, Loiret, northern France. Methods: We sampled 30 pairs of 2000‐m 2 plots, one on a road and the other 30 m inside the forest, on two road surfacing materials (limestone gravel and bare soil) and three stand ages (young, middle‐aged and mature) in Scots and Corsican pine stands in a large managed forest. Plant diversity was analysed according to life‐history traits (protection status, indigenousness, life form, habitat and ecological preferences). We tested the effects of plot position, road type and stand age on species richness, species composition and individual species response. Results: The species richness of all plant groups was always higher on roads compared to forest stands, and the forest plot communities were nearly completely nested within the roadside plot communities. Seven protected species and four non‐native potentially invasive species were observed on roadsides. Limestone‐gravelled roads hosted more species than bare soil roads, but acidophilous forest and grassland species richness was higher on bare soil roads. Plant composition similarity between the roadside and forest were higher at early successional stages and lower in older stages. Conclusions: Roads have inseparable positive and negative effects on plant communities, but the negative ones are of great concern. To prevent further damage in these nutrient‐poor ecosystems, we recommend monitoring road sections hosting protected acidophilous species, not increasing road density, and replacing limestone gravel with a low pH endogenous material. Abstract : We compared vegetation on limestone‐gravelled and bare soil forest roads in a large forest on acidic soils. We found that roads have inseparable positive and negative effects on plant communities. To prevent further damage in these nutrient‐poor ecosystems, we recommend monitoring road sections hosting protected acidophilous species, not increasing road density, and replacing limestone gravel by a low‐pH endogenous material.